Answer:
The answer is below
Step-by-step explanation:
Speed is the time rate of change of velocity, it is the ratio of distance to time.
Mr. Fowles runs at a steady 4.2 miles per hour. The time taken to cover 26 miles is:
speed = distance / time
time = distance / speed = 26 / 4.2 = 6.19 hour
I run at 3 miles per hour. I was given 3 mile lead, so the remaining distance is 23 miles (26 - 3). The time needed to complete the 23 miles is:
time = distance / speed = 23 / 3 = 7.67 hour
a) Let d be the distance Mr Fowles catches me. Hence:
time = (d + 3)/4.2; also time = d/3
(d + 3)/4.2 = d/3
3d + 9 = 4.2d
1.2d = 9
d = 7.5 miles
He would catch me at 10.5 (7.5 + 3) miles from the starting point.
b) Mr. fowles finishes after 6.19 hour. At that time, the distance is have covered is:
distance = 6.19 * 3 mi/hr = 18.57 mile
Distance behind = 23 mile - 18.57 = 4.43 mile
c) time longer = 7.67 hour - 6.19 hour = 1.48 hour
Answer:
X= 8
Y= 130
(8, 130)
Step-by-step explanation:
I used a graphing calculator to see where the two equations intersected.
Hope this helped :)
Answer:
the answer is A.) or (3 and one-half, negative 4)
Answer:
D is the answer. The graph was reflected across the y-axis, and shifted 1 unit downwards.
Step-by-step explanation:
Count the number of spaces to D, then to D'. They are the same (besides one being negative). A'B'C'D' was then shifted down 1 unit, which is why it is lower than shape ABCD.
Answer: It is only the 3rd equation that is a good example to Jeremy's argument. Others are counter examples to Jeremy's argument.
Step-by-step explanation:
Let us consider the general linear equation
Y = MX + C
On a coordinate plane, a line goes through points (0, negative 1) and (2, 0).
Slope = ( 0 - -1)/( 2- 0) = 1/2
When x = 0, Y = -1
Substitutes both into general linear equation
-1 = 1/2(0) + C
C = -1
The equations for the coordinate is therefore
Y = 1/2X - 1
Let's check the equations one after the other
y = negative one-half x minus 1
Y = -1/2X - 1
y = negative one-half x + 1
Y = -1/2X + 1
y = one-half x minus 1
Y = 1/2X - 1
y = one-half x + 1
Y = 1/2X + 1
It is only the 3rd equation that is a good example to Jeremy's argument. Others are counter examples to Jeremy's argument.